Determination of transfer pricing from the perspective of positive accounting theory - Amantara, Dodi Hendra; Utomo, Rochmad Bayu (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze how tax burden, debt covenants, and bonus mechanisms affect transfer pricing, with management ownership acting as a moderator. All international companies listed on the Indonesia Stock Exchange (IDX) that are suspected of tax disputes are the subject of this research. Using a purposive sampling technique with a research sample size of 9 international companies. The method used in this study is a quantitative method. Data were analyzed using SPSS. The research results show that tax burden and bonus mechanism have a negative and significant effect on transfer pricing, while debt covenant has a positive and significant effect on transfer pricing. Managerial ownership weakens the influence of tax burden, debt covenant, and bonus mechanism variables on transfer pricing.Tujuan dari penelitian ini adalah untuk mengetahui pengaruh beban pajak, Debt Covenant, dan mekanisme bonus terhadap transfer pricing yang dimoderasi oleh kepemilikan manajerial. Seluruh perusahaan internasional yang terdaftar di Bursa Efek Indonesia (BEI) yang terindikasi melakukan sengketa pajak merupakan subjek penelitian ini. Menggunakan teknik purposive sampling dengan jumlah sampel penelitian sebanyak 9 perusahaan internasioanal. Metode dalam penelitian ini adalah metode kuantitaif Data dianalisis menggunakan SPSS.Hasil penelitian menunjukkan bahwa beban pajak dan mekanisme bonus berpengaruh negatif dan signifikan terhadap transfer pricing dan debt covenant berpengaruh positif dan signifikan terhadap transfer pricing, kepemelikan manajerial memperlemah pengaruh variabel beban pajak, debt covenant, dan mekanisme bonus terhadap transfer pricing.